Are pro-ecological values enough? Determining the drivers and extent of participation in citizen science programs. Issue 6 (2nd November 2019) - Davis, Adrian; Taylor, Charlotte E.; Martin, John M.
ABSTRACT: Citizen science programs provide an opportunity for the public to reconnect with nature; however, pro-environmental values may not necessarily result in a high level of participation. This study assessed the values and attitudes toward ecology and conservation of 482 people, including 231 citizen scientists participating in two programs requiring either a 'complex' or 'simple' level of participation. Positive attitudes toward urban wildlife were positively associated with increased participation in citizen scientist programs; however, a pro-ecological attitude was not always associated with an increasing level of participation. Young adults were more likely to participate in the simple data submitting a program or via social media, while middle-aged and older adults from vegetated suburbs were more likely to participate in the complex data collecting multi-species focused program. These results have implications for strategic design and targeting of citizen science programs to maximize participation rates.